Dementia-friendly design of television news broadcasts. Issue 3 (16th September 2019) - Funnell, Liam; Garriock, Isabel; Shirley, Ben; Williamson, Tracey
Abstract : Purpose: The purpose of this paper is to understand factors that affect viewing of television news programmes by people living with dementia, and to identify dementia-friendly design principles for television news programmes and factors for personalising object-based media broadcast. Design/methodology/approach: Extensive public involvement comprising two discussion groups with people with dementia and family carers informed the study design and provided supplementary secondary data. Primary data collection comprised a focus group interview with people with dementia ( n =4) and family carers ( n =4). Past viewing experiences and perceived barriers and facilitators to viewing television were explored. Participants commented on an array of video clips comprising varying segments of fictional news programmes, plus control versions of each segment. Findings: Four themes were identified: content (general comments, context, type of media and pace); presenter (body language, clothing and accent); background (location and studio appearance); and technical aspects (graphics, sound, colours, camera, transitions, general issues). Research limitations/implications: Limitations included a modest sample size which is offset by exemplary public involvement in informing the study design. Practical implications: Measures ensured research involvement and participation was made accessible to people living with dementia. Social implications: Participants benefited from sharing views with peers and expressed enhanced wellbeing from knowing their participation could lead to improved television viewing, an important social occupation, for people with dementia in the future. Originality/value: This study is the first to be published which focusses on dementia-friendly television news programmes.